Impact of Sex in the Efficacy of Perioperative Desensitization Procedures in Heart Transplantation: A Retrospective Cohort Study - Nguyen, Lee S.; Salem, Joe-Elie; Bories, Marie-Cécile; Coutance, Guillaume; Amour, Julien; Bougle, Adrien; Suberbielle, Caroline; Kheav, Vissal-David; Carmagnat, Maryvonnick; Rouvier, Philippe; Kirsch, Matthias; Varnous, Shaida; et al. (Frontiers in Immunology, 2021)
Background Sensitized patients, i.e. recipients with preformed donor-specific HLA antibodies (pfDSA), are at high-risk of developing antibody-mediated rejections (AMR) and dying after heart transplantation (HTx). Perioperative desensitization procedures are associated with better outcomes but can cause sensitization, which may influence their efficacy. Methods In sensitized patients (pfDSA>1000 mean immunofluorescence (MFI) units), we assessed the effect of perioperative desensitization by comparing treated patients to a historical control cohort. Multivariable survival analyses were performed on the time to main outcome, a composite of death and biopsy-proven AMR with 5-year follow-up. Results The study included 68 patients: 31 control and 37 treated patients. There was no difference in preoperative variables between the two groups, including cumulative pfDSA [4026 (1788;8725) vs 4560 (3162;13392) MFI units, p=0.28]. The cause of sensitization was pregnancy in 24/68, 35.3%, transfusion in 61/68, 89.7%, and previous HTx in 4/68, 5.9% patients. Multivariable analysis yielded significant protective association between desensitization and events (adjusted (adj.) hazard ratio (HR)=0.44 (95% confidence interval (95CI)=0.25-0.79), p=0.006) and deleterious association between cumulative pfDSA and events [per 1000-MFI increase, adj.HR=1.028 (1.002-1.053), p=0.031]. There was a sex-difference in the efficacy of desensitization: in men (n=35), the benefit was significant [unadj.HR=0.33 (95CI=0.14-0.78); p=0.01], but not in women (n=33) [unadj.HR=0.52 (0.23-1.17), p=0.11]. In terms of the number of patients treated, in men, 2.1 of patients that were treated prevented 1 event, while in women, 3.1 required treatment to prevent 1 event. Conclusion Perioperative desensitization was associated with fewer AMR and deaths after HTx, and efficacy was more pronounced in men than women.